2021
DOI: 10.1590/pboci.2021.082
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of the Intensity and Occurrence of Postoperative Pain of Resin-Based and Bioceramic Root Canal Sealers: A Systematic Review and Meta-Analysis of Randomized Controlled Trial Studies

Abstract: To evaluate resin-and bioceramic root canal sealers affect postoperative intensity and pain occurrence. Material and Methods: From the electronic databases, PubMed, Cochrane Library, Embase, ISI have been used to perform systematic literature until September 2020. Electronic titles were managed using the Endnote X8 software. They performed searches with mesh terms. Two reviewers blindly and independently extracted data from studies that included data for data extraction. Results: A total of 186 potentially rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…A recent meta-analysis also found that the postoperative pain (POP) was not significantly different when comparing retreatment cases obturated with bioceramic sealer versus traditional gutta percha and sealer, although numerically the bioceramic group showed a higher POP value in the 24 and 48 hours period (31) . Another meta-analysis also concluded that there was no difference between the postoperative pain in resin-based and bioceramic root canal sealers at 24 and 48 hours (32) . In the current study both the age and gender did not have a significant effect on the intensity of postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis also found that the postoperative pain (POP) was not significantly different when comparing retreatment cases obturated with bioceramic sealer versus traditional gutta percha and sealer, although numerically the bioceramic group showed a higher POP value in the 24 and 48 hours period (31) . Another meta-analysis also concluded that there was no difference between the postoperative pain in resin-based and bioceramic root canal sealers at 24 and 48 hours (32) . In the current study both the age and gender did not have a significant effect on the intensity of postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
“…Previously published systematic reviews and meta-analysis [ 29 , 30 , 31 ] evaluated the postoperative pain at different time intervals, with a maximum of only seven days. Junior et al [ 29 ] were unable to perform meta-analysis for sealer extrusion and doses of medications i.e., Ibuprofen.…”
Section: Discussionmentioning
confidence: 99%
“…Junior et al [ 29 ] were unable to perform meta-analysis for sealer extrusion and doses of medications i.e., Ibuprofen. Jamali et al [ 30 ] included articles published in English only, which could lead to selection and selective outcome reporting biases. In addition, Mekhdieva et al [ 31 ] failed to provide a clear description of the inclusion and exclusion criteria used for their study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a randomized controlled clinical trial with vital and non-vital mandibular premolars and molars, Ates et al [15], found that 68 % and 59 % of patients had discomfort in teeth filled with AH Plus and I Root, respectively. In both vital and non-vital teeth, Shashirekha et al [16] evaluation of pain in apically extruded sealers did not specify the proportion of patients who had postoperative discomfort.After root canal therapy, some discomfort known as sensitivity is normal and is brought on by clamp insertion, physical stress brought on by instruments, and chemical treatments [17].To properly determine the apical constriction in the current investigation and prevent over-instrumentation and over-filling, an electronic apex finder was employed. In none of the cases was intentional sealer extrusion done.…”
Section: Discussionmentioning
confidence: 99%